End of outsourcing in Mexico: goal achieved by the current administration by 2024? - Cadena Salom, Luis David; Ramírez, Valeria Huerta (Revista Internacional de Salarios Dignos, 2023)
Transformations and eventualities have modified the different markets of an economy. In particular, labor reforms have impacted aspects such as work skills, unemployment and the questioned outsourcing. Thus, the problem addressed in this study is the implementation of subcontracting in certain sectors, and the working conditions faced by workers hired in this modality, because they can´t afford to work this way. Since there is no clear stance whether outsourcing is beneficial or not and who it benefits; In this work we are inclined to accept the fact that this type of hiring is not supported by social security, salary compensation, vacation bonuses, bonuses, among other benefits that formal jobs have. In this sense, our objective is understanding the relationship between the reduction in subcontracting and the time elapsed since the implementation of the reform. Using information from INEGI, we determined a linear regression model to establish the relationship between the hiring period and the total number of subcontracted workers. Concluding, that labor subcontracting could finalize in a total of 3.5 years from when it became official.